How have journalists been affected psychologically by their coverage of the COVID-19 pandemic? A descriptive study of two international news organisations. Issue 7 (12th July 2021) - Osmann, Jonas; Selva, Meera; Feinstein, Anthony
Abstract : Objectives: The COVID-19 pandemic has presented unprecedented healthcare challenges. Journalists covering the pandemic at close quarters are working in ways akin to first responders, but nothing to date is known of the psychological distress this is potentially causing them. This study aims to determine whether journalists reporting on the COVID-19 crisis have been affected emotionally, and if so to assess the severity of their distress. It also investigates potential demographic and work-related predictors and whether news organisations had provided counselling to their journalists. Participants: A total of 111 journalists working for two international news organisations were approached of which 73 (66%) participated in the study. Primary and secondary outcome measures: Symptoms of anxiety (Generalised Anxiety Disorder Scale-7 (GAD-7)), depression (Patient Health Questionnaire (PHQ-9)), posttraumatic stress disorder (PTSD; PTSD Checklist for DSM-5 (PCL-5)), overall psychological distress (12-item General Health Questionnaire (GHQ-12)), and treatment. Results: The percentages of journalists exceeding threshold scores for clinically significant anxiety, depression, PTSD and psychological distress were: GAD-7, 26%; PHQ-9, 20.5%; PCL-5, 9.6%; GHQ-12, 82.2%. Journalists assigned to cover the pandemic (n=54 (74%)) were significantly more anxious (p<0.05). Journalists who received counselling (n=38 (52%)) following the onset of the pandemic reported significantly fewer symptoms of anxiety (p<0.01), depression (p<0.01) and overall psychological distress (p<0.01). Conclusions: Journalists covering the COVID-19 pandemic are experiencing levels of anxiety and depression similar to those seen in first responders. Psychological therapy provided in a timely manner can significantly alleviate emotional distress.